2015
DOI: 10.4103/2319-4170.151033
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and morphometric study of proximal and distal ends of dry radii with its clinical implications

Abstract: R adial head and neck fractures constitute 1.7-5.4% of all fractures. Radial head fractures alone constitute one-third of all elbow fractures and about 20% of all elbow trauma cases.[1] An appreciation of the part played by radial head in the overall stability of elbow and forearm has encouraged several investigators to recommend conservation of radial head, either by operative fixation or by prosthetic replacement.Distal radius fractures comprise 8-15% of all upper limb fractures. So, information of normal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
5
23
0
1
Order By: Relevance
“…and Altissimi et al 25. The mean value of radial inclination of our study lies between the mean values of two Indian cadaveric studies by Gupta et al 6. and Prithishkumar et al 7.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…and Altissimi et al 25. The mean value of radial inclination of our study lies between the mean values of two Indian cadaveric studies by Gupta et al 6. and Prithishkumar et al 7.…”
Section: Discussionsupporting
confidence: 76%
“…There are very fewer studies available for the morphometry of distal radius in the Indian population 67. Hence, the unblemished intellect about the morphometry is urged for the management of DER.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many morphometric studies have been done about radius. Guptaet al, Gasse et al and Giannicola et al [10][11][12] found the length of radius as 23.5 cm, 22.9 cm and 22.1 cm, respectively. Prithishkumar et al [13] found the length of left and right radius as 24.4 cm and 24.2 cm, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Articular reduction is best evaluated by radiocarpal arthrotomy between second and fourth dorsal compartments, just distal to lister's tubercle. (8) So distance between tip of styloid process and dorsal tubercle is an important parameter. Nutrient foramen is defined as the largest of the foramina present on the shaft of the long bones and admits a nutrient artery for that bone.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%